A technical discussion of mining operations in the lime and cement industries of Zambia and Malawi - Mills, Jack (2000)
This document constitutes a brief discussion of the total concept of mining limestone, particularly for lime and cement manufacture. Actual case studies in which the writer has participated have been used to demonstrate the methods used by the various operators and their attitude to matters such as the environment has been described.